Nano-microencapsulados de extrato de Azadirachta indica usando ligninas do bagaço de cana-de-açúcar: estabilidade e eficácia contra insetos pragas - Costa, Eveline Soares (2014)
The present work aimed the development of a model bioinsecticide for pest insect control using microencapsulated botanical extracts of Azadirachta indica (neem), and natural polymer of lignins, witch were extracted from sugarcane bagasse. Several different extraction methods and chemical modifications were carried out on lignin in order to evaluate yield, cost, environmental advantages and biological efficacy. Among the proposed chemical modifications the main reactions were oxidation and acetylation. Techniques used for biopolymer characterization were FITR, 1H NMR, MALDI-TOF and SEM. Chemometric tools on NMR analyses aided on lignin differentiation according to their groups: oxidized, acetylated and naturals. Lignins were used in microencapsulation processes of extracts and fractions of the natural insecticide, A. indica L. Juss, by using Spray-Drying methods. The obtained products were subjected to thermal and photochemical degradation assays. The formulation promoted stability gains of approximately 40% for the formulated botanical extract. Use of commercial thermal and photochemical protectors were also investigated where it was observed that lignin was more efficient than traditional commercial photostabilizers protectors, showing that there is no need for adding synthetic protectors on microencapsulation process, and consequently, they are not needed on the final product. Microencapsulation was done through process known as Nanoemulsion/Solvent Displacement developed by the workgroup. In this process, botanical material was firstly nanoemulsioned, coated by a biopolymeric film in order to promote nanocapsules, and dried using Spray-Dryer generating micrometric clusters. All formulated material was subjected to biological assays to Spodoptera frugiperda, Diabrotica speciosa, Diatraea saccharalis e Anticarsia gemmatalis. Data obtained on biological testes shows that formulations that were prepared with neem and lignin were as active as non-formulated botanical extract on pest insects.